2022
DOI: 10.1108/ejtd-02-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and employee creativity: the mediating roles of work engagement and knowledge sharing

Abstract: Purpose This study aims to investigate the relationship between empowering leadership and employee creativity and the mediating roles of work engagement and knowledge sharing in this relationship. Design/methodology/approach Using the results of a survey of 302 knowledge workers from a leading telecommunications company in South Korea, the relationships among the variables empowering leadership, work engagement and knowledge sharing on employee creativity were analyzed using conducted confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 87 publications
1
14
0
1
Order By: Relevance
“…Spending too much time alone in a virtual environment without interacting with others causes a lot of problems in society [12] . The value of schooling and academic performance of student is the topmost priority of all academic institutions [29] . Internet addiction can affect people of any age, but it affects students the most severely.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Spending too much time alone in a virtual environment without interacting with others causes a lot of problems in society [12] . The value of schooling and academic performance of student is the topmost priority of all academic institutions [29] . Internet addiction can affect people of any age, but it affects students the most severely.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotional and cognitive preoccupation with the internet -It refers to a reliance on internet activities that is excessive [24] . A drive to use an online tool like a chatbox or Facebook to make oneself comfortable will often lead an individual to favor online interaction.…”
Section: B Variables Independent Variablementioning
confidence: 99%
“…perceived organizational support, leadership, culture) resources that motivate employees to engage in their work (Kossyva et al, 2022;Truong et al, 2021;Lei et al, 2021). However, this study aims to unveil how ethical leadership help employees enhance their work engagement because Joo et al (2022) suggested that the literature on leadership and work engagement is scant and needs further attention. Ethical leadership is "the demonstration of normatively appropriate conduct through personal actions and interpersonal relationships, and the promotion of such conduct to followers through two-way communication, reinforcement and decision-making" (Brown et al, 2005, p. 120).…”
Section: Introductionmentioning
confidence: 98%
“…, 2021). However, this study aims to unveil how ethical leadership help employees enhance their work engagement because Joo et al. (2022) suggested that the literature on leadership and work engagement is scant and needs further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Creativity is a feature many organizations wish to cultivate in their workforce, but it is sometimes a combined effort. Joo et al (2023) sought to identify the different ways that leadership can impact employee creativity.…”
mentioning
confidence: 99%